Preparation method of high-response miniature supercapacitor based on high-conductivity graphene
Prepare highly conductive graphene films through laser induced and carve them into high-resolution electrodes, solving the problems of complex and cost in traditional graphene processes, achieving high-efficiency and low-cost mass production of high-responsive micro-supercapacitors, and improving conductivity and scan speed.
Patent Information
- Application Number
- CN202411343925.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The traditional graphene preparation process has low yield, high cost and complex process, which cannot meet the needs of industrial and large-scale production, and the conductivity of carbon-based materials is insufficient, which affects its electrochemical performance.
A cyanate film is prepared on the substrate based on laser induction, and a high-conductive graphene film with a sintered nanoparticle morphology is formed by a large-size spot laser beam, and then engraved into high resolution through a small-size spot laser beam. The interdigital electrode combines conductive silver paste and copper foil leads and encapsulates gel electrolyte in the vacuum cavity to form a high-responsive micro-supercapacitor.
It realizes efficient and low-cost large-scale preparation of highly conductive graphene films, improves the conductivity, and can mass-produce high-response micro-supercapacitors with special purposes, with scanning speeds up to 1000V/s.
Smart Images

Figure CN119252674A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of laser micro-nano manufacturing, and in particular relates to a method for preparing a high-response micro-supercapacitor based on highly conductive graphene. Background Art
[0002] With the rapid development of electronic products and equipment, various portable smart devices have been widely used. Traditional capacitors cannot fully meet the development needs of increasingly miniaturized and highly integrated electronic devices due to their large size. Micro energy storage devices such as micro supercapacitors have become a research hotspot in the scientific field.
[0003] Micro supercapacitors (MSCs) have the advantages of small size, long life, high power density, fast charge and discharge, and excellent cycle stability. They have broad application prospects in electronic information, energy storage devices, biomedicine, thermal energy management, etc. Carbon-based materials are the most commonly used electrode materials for supercapacitors. This is because carbon-based materials have the advantages of hierarchical porous structure and high specific surface area, which can provide sufficient active sites for charge storage and facilitate the diffusion of electrolyte ions in the electrode. However, due to the limitations of precursor characteristics and preparation process, the conductivity of carbon-based materials is low, which is not conducive to improving their electrochemical performance. The conductivity of carbon-based materials is the result of the combined influence of multiple factors, including but not limited to pore structure, heteroatom content, degree of graphitization, etc. High conductivity is crucial to the rate capability and response capability of carbon-based materials. Therefore, there is an urgent need for a method that can stably prepare highly conductive graphene.
[0004] Traditional methods for preparing graphene structures mainly include chemical vapor deposition, mechanical exfoliation, chemical exfoliation, etc. These preparation processes have the disadvantages of low yield, high cost, and complex process, and cannot meet the requirements of industrial and large-scale production. In recent years, with the development of simple and fast laser-induced graphene technology (LIG), people have begun to look for all carbon precursors that can be transformed into graphene, in order to prepare high-quality graphene quickly and at low cost.
[0005] Therefore, the present invention provides a method for preparing a high-response micro supercapacitor based on highly conductive graphene to solve the above technical problems. Summary of the invention
[0006] In view of the above problems, the object of the present invention is to provide a method for preparing a high-response micro supercapacitor based on highly conductive graphene, which has low cost, high efficiency and can be prepared on a large scale.
[0007] The present invention provides a method for preparing a high-response micro-supercapacitor based on highly conductive graphene, comprising the following steps:
[0008] S1, providing a substrate, performing surface modification on the substrate; and preparing a cyanate ester film on the surface-modified substrate;
[0009] S2, irradiating the cyanate film with a large-size spot laser beam to induce the cyanate film to form a highly conductive graphene film with a sintered nanoparticle-like morphology;
[0010] S3, engraving the highly conductive graphene film by a small-size spot laser beam to obtain a high-resolution interdigital electrode;
[0011] S4, use conductive silver paste and copper foil to lead out the pins of the high-resolution interdigital electrodes, and clean and dry the high-resolution interdigital electrodes after the pins are led out; evenly coat the dried high-resolution interdigital electrodes with gel electrolyte, and place the high-resolution interdigital electrodes coated with gel electrolyte in a vacuum chamber for vacuum treatment; use a packaging film to encapsulate the high-resolution interdigital electrodes after vacuum treatment to obtain a high-response micro supercapacitor.
[0012] Preferably, the surface modification in S1 is a radiation irradiation method, and an array microstructure pattern with a single size of less than 100 μm is processed on the surface of the substrate by ultraviolet laser.
[0013] Preferably, the wavelength of the ultraviolet laser is 355nm, the pulse frequency is 600Hz, and the pulse duration is 10ps; the scanning direction of the ultraviolet laser is progressive from left to right and from top to bottom, the scanning spacing is 50μm-100μm, the scanning speed is 600mm / s-1200mm / s, and the power is 50%-70% of the peak power of 17.5W.
[0014] Preferably, the substrate is selected from any one of glass, quartz, silicon, and a flexible substrate, and the thickness of the substrate is 0.01 mm-0.2 mm.
[0015] Preferably, the step of preparing a cyanate ester film on the surface-modified substrate in S1 specifically includes: S11, providing a cyanate ester monomer, and heating the cyanate ester monomer in a water bath to obtain a liquid cyanate ester monomer; S12, uniformly coating the liquid cyanate ester monomer on the surface of the surface-modified substrate; S13, performing a high-temperature thermal curing treatment on the substrate coated with the liquid cyanate ester monomer, so that the liquid cyanate ester monomer is converted into a cyanate ester film and cured on the substrate.
[0016] Preferably, the water bath heating temperature in S11 is 50°C-70°C, and the heating time is 20min-30min; the coating method of the liquid cyanate monomer in S12 is a drip coating method and a weighing method; the temperature condition of the high-temperature thermal curing treatment in S13 is 25°C-250°C, and the treatment time is 5h-6h.
[0017] Preferably, the large-size spot laser beam is emitted by a mid-infrared CO2 laser or a visible light semiconductor laser, and the spot size of the large-size spot laser beam is 200 μm-500 μm; the scanning mode of the mid-infrared CO2 laser or the visible light semiconductor laser is a left-to-right grating overlapping line-by-line scanning mode, the scanning speed is 60 mm / s-200 mm / s, the defocus amount is between +1 mm and +5 mm, the scanning pixel step is 800 dots / inch (DPI)-1200 dots / inch (DPI), and the product of the spot size of the large-size spot laser beam and the scanning pitch is between 5000 μm. 2 -8000μm 2 .
[0018] Preferably, the small-size spot laser beam is emitted by an ultraviolet ultrafast laser or an ultraviolet nanolaser, and the spot size of the small-size spot laser beam is less than 20 μm; the ultraviolet ultrafast laser or ultraviolet nanolaser adopts an alternating direction laser beam movement path, a scanning speed between 600 mm / s-1500 mm / s, a scanning pitch less than 8 μm, a scanning number of not less than 2 times, and a power of 80%-95% of the peak power of 17.5 W.
[0019] Preferably, the solvents for cleaning the high-resolution interdigital electrodes after the lead pins are anhydrous ethanol and deionized water; the temperature conditions for drying the cleaned high-resolution interdigital electrodes are 50°C-90°C, and the drying time is 10min-30min; the gel electrolyte is any one of PVA / H3PO4 gel electrolyte, PVA / H2SO4 gel electrolyte and PVA / LiCl gel electrolyte, the vacuum degree of the vacuum treatment is -0.9MPa~-0.7MPa, and the time of the vacuum treatment is 20min-40min.
[0020] Preferably, the packaging film is a polyimide film (PI) or a polyethylene terephthalate film (PET), and the thickness of the packaging film is 25 μm-80 μm.
[0021] Compared with the related art, the present invention provides a method for preparing a high-response micro-supercapacitor based on highly conductive graphene, comprising the following steps: providing a substrate and performing surface modification on the substrate; preparing a cyanate film on the substrate; irradiating the cyanate film with a large-size spot laser beam to induce the cyanate film to form a highly conductive graphene film with a sintered nanoparticle-like morphology; engraving the highly conductive graphene film with a small-size spot laser beam to obtain a high-resolution interdigital electrode; using a conductive silver paste and copper foil to lead out the pins of the high-resolution interdigital electrode, and cleaning and drying the high-resolution interdigital electrode after the pins are led out; uniformly coating a gel electrolyte on the dried high-resolution interdigital electrode, and vacuumizing the electrode; and using a packaging film to encapsulate the vacuumized high-resolution interdigital electrode to obtain a high-response micro-supercapacitor. The above preparation method can be used to induce the generation of highly conductive graphene films with sintered nanoparticle-like morphology on any substrate. If the substrate is a polymer substrate, the sheet resistance of the graphene film is as low as 1.7Ω / square (converted into a conductivity of about 122.5S / cm); if the substrate is a metal substrate, the sheet resistance of the graphene film is as low as 1.6Ω / square (converted into a conductivity of>130S / cm); in addition, the highly conductive graphene films with sintered nanoparticle-like morphology generated on the substrate are all formed by laser processing, which has high generation efficiency, low cost, excellent conductive properties, and can be prepared in large quantities. By patterning on the highly conductive graphene film, a high-response micro-supercapacitor with special uses can be obtained; and the scanning speed of the high-response micro-supercapacitor prepared using the highly conductive graphene film can reach a maximum of 1000V / s. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic flow chart of a method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to the present invention;
[0023] Figure 2 is a schematic diagram of the process of preparing a cyanate ester film on the substrate after surface modification in S1;
[0024] Figure 3 This is a schematic diagram of the technical solution for preparing a high-response micro-supercapacitor according to Example 1;
[0025] Figure 4 is a microscope image of the substrate after surface modification in Example 1 and Example 2;
[0026] Figure 5 is a comparison diagram of the resistance of highly conductive graphene films obtained by processing under the same parameters in Example 1 and Example 2;
[0027] Figure 6is a schematic diagram of high-resolution interdigital electrode engraving patterns prepared in Example 1 and Example 2;
[0028] Figure 7 is a schematic diagram of the microscopic morphology of the surface of the highly conductive graphene film described in Example 1 and Example 2;
[0029] Figure 8 is a CV curve diagram of the high-response micro supercapacitor prepared in Example 1 at a scan rate of 50 V / s;
[0030] Fig. 9 is a CV curve diagram of the high-response micro supercapacitor prepared in Example 2 at a scan rate of 50 V / s;
[0031] Fig.10 This is a CV curve diagram of the high-response micro supercapacitor prepared in Example 2 at a scan rate of 1000 V / s. DETAILED DESCRIPTION
[0032] The present invention provides a method for preparing a high-response micro supercapacitor based on highly conductive graphene, aiming to solve the problems of low yield, high cost and complex process of traditional graphene preparation process, which cannot meet the requirements of industrialized and large-scale production.
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Please also refer to the attached Figure 1-2 The present invention provides a method for preparing a high-response micro-supercapacitor based on highly conductive graphene, comprising the following steps:
[0035] S1, providing a substrate, performing surface modification on the substrate; and preparing a cyanate ester film on the surface-modified substrate.
[0036] In this embodiment, the surface modification is a ray irradiation method, in which an array microstructure pattern with a single size of less than 100 μm is processed on the substrate surface by ultraviolet laser to improve the wettability of the substrate surface; and the wavelength of the ultraviolet laser is 355 nm, the pulse frequency is 600 Hz, and the pulse duration is 10 ps; the scanning direction of the ultraviolet laser is from left to right and from top to bottom, the scanning spacing is 50 μm-100 μm, the scanning speed is 600 mm / s-1200 mm / s, and the power is 50%-70% of the peak power of 17.5 W. Specifically, this method uses laser surface microstructuring technology, that is, using the high energy peak intensity and nonlinear absorption characteristics of the laser, the picosecond laser pulse width (1 ps = 10 -12 ) is much smaller than the electron lattice relaxation time of the processed material (10 -10 ~10 -12 s), the electrons complete the absorption of photon energy before the lattice heats up. Therefore, during the processing, the electrons and the lattice are in a non-equilibrium state, which inhibits heat diffusion, thereby greatly reducing the heat-affected zone, reducing the thickness of the recast layer, and reducing surface microcracks, ultimately achieving high-precision and high-quality processing of the material and preparing a surface hydrophilic microstructure.
[0037] Specifically, the substrate is selected from any one of glass, quartz, silicon, and a flexible substrate, such as polyimide film / paper, titanium foil, nickel foil, copper foil, non-woven carbon cloth, etc., and the thickness of the substrate is 0.01mm-0.2mm. It should be noted that the type and thickness of the substrate are set after a large number of experiments, because the type and thickness of the substrate ultimately affect the thermal conductivity of the composite material. Under the same processing conditions, the thermal conductivity of the composite material is better, and the uniformity and degree of graphitization of the graphene surface finally formed are higher; at the same time, the thickness should not be too thick or too thin. Too thick will easily cause most of the laser energy to be absorbed by other parts of the material, and not absorbed by the cyanate ester. Too thin thermal conductive layer will cause the resin to absorb energy exceeding the vaporization temperature, resulting in graphene transition oxidation and shedding phenomenon.
[0038] In this embodiment, the cyanate ester film is prepared on the surface-modified substrate in S1, which specifically includes: S11, providing a cyanate ester monomer, and heating the cyanate ester monomer in a water bath to obtain a liquid cyanate ester monomer; S12, uniformly coating the liquid cyanate ester monomer on the surface of the surface-modified substrate; S13, performing a high-temperature thermal curing treatment on the substrate coated with the liquid cyanate ester monomer, so that the liquid cyanate ester monomer is converted into a cyanate ester film and cured on the substrate. Furthermore, the cyanate monomer is solid at room temperature, and a liquid cyanate monomer with good fluidity can be obtained by heating in a water bath, which is convenient for subsequent coating of the substrate. Therefore, the temperature of the water bath heating in S11 is set to 50°C-70°C, and the heating time is 20min-30min; the coating method of the liquid cyanate monomer in S12 is a drop coating method and a weighing method, and the amount of drop addition is controlled by the weighing method to determine the thickness of the final film; the temperature condition of the high-temperature thermal curing treatment in S13 is 25°C-250°C, and the treatment time is 5h-6h. After naturally cooling to room temperature, a cyanate film with uniform surface thickness can be obtained.
[0039] S2, irradiating the cyanate film with a large-size spot laser beam to induce the cyanate film to form a highly conductive graphene film with a sintered nanoparticle-like morphology.
[0040] In this embodiment, the large-size spot laser beam is emitted by a mid-infrared CO2 laser or a visible light semiconductor laser, and the spot size of the large-size spot laser beam is 200 μm-500 μm; during the laser induction process, the laser scanning mode of the mid-infrared CO2 laser or the visible light semiconductor laser is a left-to-right grating overlapping line-by-line scanning mode, the scanning speed is 60 mm / s-200 mm / s, the defocus amount is between +1 and +5 mm, the scanning pixel step is 800 dots / inch (DPI)-1200 dots / inch (DPI), and the product of the spot size of the large-size spot laser beam and the scanning pitch is between 5000 μm. 2 -8000μm 2 In addition, for the mid-infrared CO2 laser, a mid-infrared CO2 laser with a laser power greater than 16W, a defocus of -2mm, a scanning speed of 100mm / s, and a scanning pixel step of 1000DPI (25.4μm pitch) is preferred, and its processing effect is the best.
[0041] It is worth mentioning that cyanate ester can be graphitized by using a large-size spot laser beam and a low laser scanning speed. The principle is that the cyanate ester material itself has a high absorption rate for infrared wavelength lasers, and the substrate material with high thermal conductivity and electrical conductivity can quickly convert the absorbed laser energy into thermal energy. In a high temperature and high pressure environment, the lattice of the cyanate ester polymer begins to pyrolyze, and eventually releases some C, O, N and other atoms in the form of gas, while the remaining C atoms begin to self-heal to form a stable six-ring (benzene ring) structure. The rings are interconnected and eventually graphitized.
[0042] S3, engraving the highly conductive graphene film by a small-size spot laser beam to obtain a high-resolution interdigital electrode.
[0043] In this embodiment, the small-size spot laser beam is emitted by an ultraviolet ultrafast laser or an ultraviolet nano-laser, and the spot size of the small-size spot laser beam is less than 20μm; during the laser engraving process, especially in the extremely small-size ablation process, the ultraviolet ultrafast laser or ultraviolet nano-laser adopts a laser beam moving path with alternating directions, a scanning speed between 600mm / s-1500mm / s, a scanning interval of less than 8μm, a scanning number of not less than 2 times, and a power of 80%-95% of the peak power of 17.5W. Preferably, an ultraviolet picosecond laser with a pulse center wavelength of 355nm and a pulse width of 10ps is used, and the parameters are set to a scanning speed of 600mm / s-800mm / s, a scanning interval of 4μm, a scanning number of 3 times, and a laser power of 15-16W, which has the best processing effect.
[0044] Furthermore, an ultrafast pulsed ultraviolet laser with a small spot size, high peak power, short pulse width, and high laser scanning speed is used. The purpose is to utilize the characteristics of the instantaneous high peak power of the ultrafast pulsed laser to quickly heat up, vaporize, sublimate, and cool the processed part, while leaving a pattern of high-resolution interdigitated electrodes on the unprocessed part.
[0045] S4, use conductive silver paste and copper foil to lead out the pins of the high-resolution interdigital electrodes, and clean and dry the high-resolution interdigital electrodes after the pins are led out; evenly coat the dried high-resolution interdigital electrodes with gel electrolyte, and place the high-resolution interdigital electrodes coated with gel electrolyte in a vacuum chamber for vacuum treatment; use a packaging film to encapsulate the high-resolution interdigital electrodes after vacuum treatment to obtain a high-response micro supercapacitor.
[0046] Furthermore, in S4, the solvents used to clean the high-resolution interdigital electrodes after the lead pins are anhydrous ethanol and deionized water; the temperature conditions for drying the cleaned high-resolution interdigital electrodes are 50°C-90°C, and the drying time is 10min-30min; the gel electrolyte is any one of PVA / H3PO4 gel electrolyte, PVA / H2SO4 gel electrolyte and PVA / LiCl gel electrolyte, the vacuum degree of the vacuum treatment is -0.9MPa to -0.7MPa, and the time of the vacuum treatment is 20min-40min. The purpose of maintaining the vacuum for a certain period of time is to discharge the gaps between the high-resolution interdigital electrodes themselves and the gas molecules in the gel electrolyte, so that the gel electrolyte and the high-resolution interdigital electrodes are in full contact. In addition, in this embodiment, the vacuum treatment is carried out in a vacuum chamber, and the vacuum chamber is a vacuum drying oven.
[0047] In this embodiment, the packaging film is a polyimide film (PI) or a polyethylene terephthalate film (PET), and the thickness of the packaging film is 25 μm-80 μm.
[0048] Please also refer to the attached Figure 3-10 In order to further illustrate the present invention, two specific embodiments are provided for illustration.
[0049] Example 1
[0050] 1. Providing a PI substrate, performing surface modification on the PI substrate; and preparing a cyanate ester film on the surface-modified PI substrate.
[0051] In this embodiment, a 125 μm thick Kapton PI film is cut into 50 mm × 50 mm pieces, flatly attached to a glass sheet, then cleaned with anhydrous ethanol, rinsed with deionized water, and dried in a 50°C vacuum oven for 15 min. Then, it is placed in the center of the workbench, and the CAD pattern is imported and the laser parameters are set. A UV picosecond laser with a pulse center wavelength of 355 nm, a pulse duration of 10 ps at a basic repetition of 600 Hz is used to process from left to right and from top to bottom, with a scanning spacing of 50 μm, a laser power of 60% of the peak power of 17.5 W, and a scanning speed of 600 mm / s is used to improve the wettability of the surface of the PI substrate. At this time, the sample is in the position where the z-axis spot of the laser is the smallest and the energy is most concentrated. The solid cyanate monomer is placed in a 70°C water bath in advance, and a liquid cyanate monomer is obtained after 30 minutes. Place the PI substrate on a balance, slowly drip 0.5g of liquid cyanate monomer onto the processed area on the surface of the PI substrate, and then use a small stick to scrape the surface to spread it evenly. Transfer it to the heating table, set the temperature and heating time so that the heating table rises from 25°C to 250°C within 5h, and then cool it naturally to obtain a cyanate film solidified on the PI substrate.
[0052] 2. Irradiating the cyanate film with a large-size spot laser beam to induce the cyanate film to form a highly conductive graphene film with a sintered nanoparticle-like morphology.
[0053] In this embodiment, a cyanate film on a PI substrate is placed on a workbench, and a continuous CO2 laser (10.6 μm) cutting machine with a rated power of 50 W and a beam diameter of 250 μm is selected to perform laser-induced graphene on the cyanate film. During the laser induction process, a laser direct writing scan with a defocus of -2 mm is used to scan the cyanate film. The laser scanning method is a grating overlapped line-by-line scan from left to right. The laser power is 16 W, the scanning speed is 100 mm / s, and the scanning pixel step size is 1000 DPI, so that the cyanate film is transformed into a highly conductive graphene film.
[0054] 3. Carving the highly conductive graphene film by a small-size spot laser beam to obtain a high-resolution interdigital electrode;
[0055] In this embodiment, the obtained highly conductive graphene film is placed on a workbench, and the CAD pattern is imported into the control center. A UV picosecond laser with a pulse center wavelength of 355 nm and a pulse duration of ~10 ps at a basic repetition of 600 Hz is used. The laser scanning mode is from left to right and from top to bottom. The laser power is 90% of the peak power of 17.5 W, the scanning speed is 600 mm / s, the scanning gap is 4 μm, and the scanning number is 3 times to engrave a high-resolution interdigital electrode pattern.
[0056] 4. Use conductive silver paste and copper foil to lead out the pins of the high-resolution interdigital electrodes, and clean and dry the high-resolution interdigital electrodes after the pins are led out; evenly coat the dried high-resolution interdigital electrodes with gel electrolyte, and place the high-resolution interdigital electrodes coated with gel electrolyte in a vacuum chamber for vacuum treatment; use a packaging film to encapsulate the high-resolution interdigital electrodes after vacuum treatment to obtain a high-response micro supercapacitor.
[0057] In this embodiment, the high-resolution interdigital electrode is cleaned with anhydrous ethanol and deionized water, and dried for 15 minutes at a temperature of 50°C. Polyvinyl alcohol (PVA, AH-26, SCR) is mixed with deionized water and H2SO4 (95%, Sigma-Aldrich) (1g PVA / 10ml H2O / 1g H2SO4) at 85°C for about 1h to prepare a PVA / H2SO4 ion gel electrolyte. Finally, 0.20mL of ion gel electrolyte is dripped into the gap between the high-resolution interdigital electrodes, placed in a vacuum chamber and maintained at a vacuum degree of ~0.8Mpa for 30min, and the gas molecules in the gap between the high-resolution interdigital electrodes themselves and the gel electrolyte are extracted. After being taken out, they are placed in a constant temperature dryer (25°C) overnight to remove excess moisture. Conductive silver paste and copper foil are used to lead out the pins, and then a PI film with a thickness of 50μm is used for encapsulation to obtain a micro supercapacitor.
[0058] Example 2
[0059] 1. Providing a metal substrate, performing surface modification on the metal substrate; and preparing a cyanate ester film on the surface-modified metal substrate.
[0060] In this embodiment, the material of the metal substrate is titanium foil. The 0.03 mm thick titanium foil is cut into pieces of 50 mm × 50 mm in size, flatly attached to a glass sheet, then cleaned with anhydrous ethanol, rinsed with deionized water, and dried in a 50°C vacuum oven for 15 minutes. Then placed in the center of the workbench, by importing the CAD pattern and setting the laser parameters, using a UV picosecond laser with a pulse center wavelength of 355 nm, a pulse duration of ~10 ps at a basic repetition of 600 Hz, and a scanning interval of 50 μm, a laser power of 60% of the peak power of 17.5 W, and a scanning speed of 600 mm / s to improve the wettability of the titanium foil surface. The sample is at the smallest z-axis spot of the laser and the most concentrated energy position. The solid cyanate monomer is placed in a 70°C water bath in advance, and a liquid cyanate monomer is obtained after 30 minutes. Place the metal substrate on a balance, slowly drip 0.5g of liquid cyanate monomer onto the processed area on the metal substrate surface, and then use a small stick to scrape the surface to make it evenly spread. Transfer to a heating table, set the temperature and heating time so that the heating table rises from 25°C to 250°C within 5h, and then cool naturally to obtain a cyanate film solidified on the metal substrate.
[0061] 2. Irradiating the cyanate film with a large-size spot laser beam to induce the cyanate film to form a highly conductive graphene film with a sintered nanoparticle-like morphology.
[0062] In this embodiment, a cyanate film on a metal substrate is placed on a workbench, and a continuous CO2 laser (10.6 μm) with a maximum power of 50 W and a beam diameter of 250 μm is used to cut the cyanate film for laser-induced graphene. During the laser induction process, a laser direct writing scan with a defocus of +2 mm is used to scan the cyanate film. The laser scanning method is a grating overlapped line-by-line scan from left to right. The laser power is 16 W, the scanning speed is 100 mm / s, and the scanning pixel step is 1000 DPI, so that the cyanate film is transformed into a highly conductive graphene film.
[0063] 3. The highly conductive graphene film is engraved by a small-size spot laser beam to obtain high-resolution interdigital electrodes.
[0064] In this embodiment, the obtained highly conductive graphene film is placed on a workbench, and the CAD pattern is imported into the control center. A UV picosecond laser with a pulse center wavelength of 355 nm and a pulse duration of ~10 ps at a basic repetition of 600 Hz is used. The laser scanning mode is from left to right and from top to bottom. The laser power is 90% of the peak power of 17.5 W, the scanning speed is 600 mm / s, the scanning gap is 4 μm, and the scanning number is 3 times to engrave a high-resolution interdigital electrode pattern.
[0065] 4. Use conductive silver paste and copper foil to lead out the pins of the high-resolution interdigital electrodes, and clean and dry the high-resolution interdigital electrodes after the pins are led out; evenly coat the dried high-resolution interdigital electrodes with gel electrolyte, and place the high-resolution interdigital electrodes coated with gel electrolyte in a vacuum chamber for vacuum treatment; use a packaging film to encapsulate the high-resolution interdigital electrodes after vacuum treatment to obtain a high-response micro supercapacitor.
[0066] In this embodiment, the high-resolution interdigital electrode is cleaned with anhydrous ethanol and deionized water, and dried at a temperature of 50°C for 15 minutes. Polyvinyl alcohol (PVA, AH-26, SCR) is mixed with deionized water and H2SO4 (98%, Sigma-Aldrich (1g PVA / 10ml H2O / 1g H2SO4) at 85°C for about 1h to prepare a PVA / H2SO4 ion gel electrolyte. Finally, -0.20mL of ion gel electrolyte is dripped into the gap between the high-resolution interdigital electrodes, placed in a vacuum chamber to maintain a vacuum degree of ~-0.8Mpa for 30min, and the gas molecules in the gap between the high-resolution interdigital electrodes themselves and the gel electrolyte are extracted. After being taken out, they are placed in a constant temperature dryer (25°C) overnight to remove excess moisture. Conductive silver paste and copper foil are used to lead out the pins, and then a 50μm thick encapsulation film is used for encapsulation to obtain a micro supercapacitor.
[0067] Compared with the related art, the present invention provides a method for preparing a high-response micro-supercapacitor based on highly conductive graphene, comprising the following steps: providing a substrate and performing surface modification on the substrate; preparing a cyanate film on the substrate; irradiating the cyanate film with a large-size spot laser beam to induce the cyanate film to form a highly conductive graphene film with a sintered nanoparticle-like morphology; engraving the highly conductive graphene film with a small-size spot laser beam to obtain a high-resolution interdigital electrode; using a conductive silver paste and copper foil to lead out the pins of the high-resolution interdigital electrode, and cleaning and drying the high-resolution interdigital electrode after the pins are led out; uniformly coating a gel electrolyte on the dried high-resolution interdigital electrode, and vacuumizing the electrode; and using a packaging film to encapsulate the vacuumized high-resolution interdigital electrode to obtain a high-response micro-supercapacitor. The above preparation method can be used to induce the generation of highly conductive graphene films with sintered nanoparticle-like morphology on any substrate. If the substrate is a polymer substrate, the sheet resistance of the graphene film is as low as 1.7Ω / square; if the substrate is a metal substrate, the sheet resistance of the graphene film is as low as 1.6Ω / square; in addition, the highly conductive graphene films with sintered nanoparticle-like morphology generated on the substrate are all formed by laser processing, which has high generation efficiency, low cost, excellent conductive properties, and can be prepared in large quantities. By patterning on the highly conductive graphene film, a high-response micro-supercapacitor with special uses can be obtained; and the scanning speed of the high-response micro-supercapacitor prepared using the highly conductive graphene film can reach a maximum of 1000V / s.
[0068] It should be noted that the above-described embodiments should be understood as illustrative rather than limiting the scope of protection of the present invention, and the scope of protection of the present invention shall be subject to the claims. For those skilled in the art, some non-essential improvements and adjustments made to the present invention still fall within the scope of protection of the present invention without departing from the essence and scope of the present invention.
Claims
1. A method for preparing a high-response micro-supercapacitor based on highly conductive graphene, characterized in that: The method comprises the following steps: S1, providing a substrate, performing surface modification on the substrate; and preparing a cyanate ester film on the surface-modified substrate; S2, irradiating the cyanate film with a large-size spot laser beam to induce the cyanate film to form a highly conductive graphene film with a sintered nanoparticle-like morphology; S3, engraving the highly conductive graphene film by a small-size spot laser beam to obtain a high-resolution interdigital electrode; S4, using conductive silver paste and copper foil to lead out the pins of the high-resolution interdigital electrodes, and cleaning and drying the high-resolution interdigital electrodes after the pins are led out; uniformly coating the dried high-resolution interdigital electrodes with gel electrolyte, and placing the high-resolution interdigital electrodes coated with gel electrolyte in a vacuum chamber for vacuum treatment; The high-resolution interdigital electrodes after vacuum treatment are packaged with a packaging film to obtain a high-response micro-supercapacitor.
2. The method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to claim 1, characterized in that: The surface modification in S1 is a radiation irradiation method, in which an array microstructure pattern with a single size of less than 100 μm is processed on the surface of the substrate by ultraviolet laser.
3. The method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to claim 2, characterized in that: The wavelength of the ultraviolet laser is 355nm, the pulse frequency is 600Hz, and the pulse duration is 10ps; the scanning direction of the ultraviolet laser is progressive from left to right and from top to bottom, the scanning spacing is 50μm-100μm, the scanning speed is 600mm / s-1200mm / s, and the power is 50%-70% of the peak power of 17.5W.
4. The method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to claim 1, characterized in that: The substrate is selected from any one of glass, quartz, silicon, and a flexible substrate, and the thickness of the substrate is 0.01 mm-0.2 mm.
5. The method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to claim 1, characterized in that: The step of preparing a cyanate film on the surface-modified substrate in S1 specifically includes: S11, providing a cyanate monomer, and heating the cyanate monomer in a water bath to obtain a liquid cyanate monomer; S12, uniformly coating the liquid cyanate monomer on the surface of the surface-modified substrate; and S13, performing a high-temperature thermal curing treatment on the substrate coated with the liquid cyanate monomer, so that the liquid cyanate monomer is converted into a cyanate film and cured on the substrate.
6. The method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to claim 5, characterized in that: The water bath heating temperature in S11 is 50°C-70°C, and the heating time is 20min-30min; the coating method of the liquid cyanate monomer in S12 is a drop coating method and a weighing method; the temperature condition of the high temperature thermal curing treatment in S13 is 25°C-250°C, and the treatment time is 5h-6h.
7. The method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to claim 1, characterized in that: The large-size spot laser beam is emitted by a mid-infrared CO2 laser or a visible light semiconductor laser, and the spot size of the large-size spot laser beam is 200 μm-500 μm; the scanning mode of the mid-infrared CO2 laser or the visible light semiconductor laser is a left-to-right grating overlapping line-by-line scanning mode, the scanning speed is 60 mm / s-200 mm / s, the defocus amount is between +1 and +5 mm, the scanning pixel step is 800 dots / inch (DPI)-1200 dots / inch (DPI), and the product of the spot size of the large-size spot laser beam and the scanning spacing is between 5000 μm 2 -8000μm 2 .
8. The method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to claim 1, characterized in that: The small-size spot laser beam is emitted by an ultraviolet ultrafast laser or an ultraviolet nanolaser, and the spot size of the small-size spot laser beam is less than 20 μm; the ultraviolet ultrafast laser or ultraviolet nanolaser adopts an alternating direction laser beam movement path, a scanning speed between 600 mm / s-1500 mm / s, a scanning spacing less than 8 μm, a scanning number of not less than 2 times, and a power of 80%-95% of a peak power of 17.5 W.
9. The method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to claim 1, characterized in that: In S4, the solvents for cleaning the high-resolution interdigital electrodes after the lead pins are anhydrous ethanol and deionized water; the temperature conditions for drying the cleaned high-resolution interdigital electrodes are 50°C-90°C, and the drying time is 10min-30min; the gel electrolyte is any one of PVA / H3PO4 gel electrolyte, PVA / H2SO4 gel electrolyte and PVA / LiCl gel electrolyte, the vacuum degree of the vacuum treatment is -0.9MPa~-0.7MPa, and the time of the vacuum treatment is 20min-40min.
10. The method for preparing a high-response micro-supercapacitor based on highly conductive graphene according to claim 1, characterized in that: The packaging film is a polyimide film (PI) or a polyethylene terephthalate film (PET), and the thickness of the packaging film is 25 μm-80 μm.
Citation Information
Patent Citations
Method and equipment for repairing short circuit of printed circuit board by using laser
CN114521061A
Micro-nano porous graphene-based planar micro supercapacitor and preparation method thereof
CN114843120A
Cited By
Filtering supercapacitor based on nanoparticle-shaped graphene / foam metal and preparation method thereof
CN120954896A
A nanoparticle graphene / foam metal-based filtering supercapacitor and a preparation method thereof
CN120954896B